Digital Entrepreneurship of Vocational Educations: Enthusiasm Level and Entrepreneurial Personality of Students - Rizal, Yosi; Putu Sudira; Farid Mutohhari (Journal of Education Technology, 2022)
Rapid development of fashion industry affected by digital technology has produced major opportunity in entrepreneurship. Significant obstacles that shall be solved are enthusiasm and student’s personality in entrepreneurship. Process of digitalization dominated in business sector has become solution that can be integrated in vocational education. This research aims to measure level of enthusiasm and entrepreneurial personality of vocational students. Descriptive research with qualitative method is used to quantify the level. 198 students from vocational educations are participated as respondents in this research. Four-Likert-scale questionnaire is applied as data collecting tool. Descriptive statistic is applied to analyze the level of enthusiasm and entrepreneurial personality of students. Meanwhile, independent sample T-test is applied to compare the two levels. The result of research reveals that high average level of enthusiasm and entrepreneurial personality of students in vocational educations that are implemented digital entrepreneur of 75,56%, while it is inversely proportional to vocational educations that do not apply of 70,51%. The process of entrepreneur in vocational education with integrated digital technology becomes innovative way that should be done while digitalization is getting stronger, so that enthusiasm and entrepreneurial personality can be improved.